Detection of wave activity in measurements of thermospheric vertical winds and temperatures at subauroral latitudes - Schmidt, Anneliese L.; Meriwether, John W.; Cooper, Matthew B.; Gerrard, Andrew J.; Goodwin, Lindsay V.; Zhang, Shun-Rong; Ye, Ying (Frontiers in Astronomy and Space Sciences, 2025)
The need for high precision measurements of vertical winds with uncertainties on the scale of 3–5 m s−1 and a temporal cadence of 1–2 min to achieve detection of gravity wave (GW) structure has made it exceedingly difficult to study the response of the thermosphere to the propagation of GW activity. Herein we present subauroral, midlatitude thermospheric wind and temperature observations using redline 630 nm measurements obtained with a 15 cm narrow field Fabry-Pérot Interferometer (FPI), named the Hot Oxygen Doppler Imager (HODI). These measurements were obtained in a first light campaign at Jeffer Observatory (41.03°N, 74.83°W) located in Jenny Jump State Forest in northwestern New Jersey. The heightened sensitivity of HODI enables analysis of observations with uncertainties of approximately 3–5 m s−1 for vertical wind speeds and 10–15 K for temperatures for 2-min exposures. Data was collected during periods of both geomagnetically quiet and active conditions, and GW structures were seen in both data sets. One detailed observation, taken the night of 25 July 2022, enabled the ≈90° phase shift between vertical winds and temperatures to be inferred, as per standard GW polarization relations with weak viscous dissipation. However, most other observations are found to have little correlation between the two series of temperature and vertical wind. We interpret this to be a result of the propagation and interaction of multiple GW events superimposed upon one another. Wave-like structures in the ionosphere observed in differential total electron count maps, or traveling ionospheric disturbances (TIDs), are often related to GW induced processes, and we provide comparisons of selected wave events observed by HODI to TIDs. These results suggest in a general sense that a relationship may exist between wave fluctuations seen in both the neutral atmosphere and the ionosphere. However, we suggest that the 35–70 km vertical extent of the 630 nm nightglow layer combined with an environment of multiple GW events with differing propagation speeds and vertical wavelengths may have the effect of diminishing or eliminating possible existing temperature and vertical wind correlation.